The Influence of the Application of Information Technology and the Implementation of Internal Control on the Quality of Accounting Information Systems (Study On Textile Company Pt. Budi Agung Sentosa - Ari Bramasto (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
The need for information depends on various factors, including the information technology used, but the application of technology in producing information should consider the user. The purpose of this study was to determine the effect of the application of information technology and the implementation of internal control on the quality of accounting information systems at PT. Budi Agung Sentosa. The method used is a descriptive verification approach. the population in this study were employees of PT. Budi Agung Sentosa as many as 50 people where the sampling method used was saturated sampling. The data analysis used is multiple regression analysis. The results show that the application of information technology has a positive and significant impact on the quality of the accounting information system at PT Budi Agung Sentosa by 67.7%. The implementation of internal control has a positive and significant effect on the quality of the accounting information system at PT Budi Agung Sentosa by 62.5% and simultaneously the application of information technology and the implementation of internal control together has a significant effect on the quality of the accounting information system at PT Budi Agung Sentosa with a large the effect of 73.6% while the remaining 26.4% is influenced by other factors that are not observed.